Suppression of interference for DVB-T2 signals - Tan, Song Khai (Nanyang Technological University, 2020)
This research project focuses on interferences encountered by Digital Video Broadcasting – Second Generation Terrestrial (DVB-T2) during broadcast transmission. The structure of DVB-T2 signal is learnt through the review of DVB-T2 transmitter model. Several types of interferences, including AWGN, channel fading, co-channel interference and jamming effect are incorporated into the system. Simulation is done on Common Simulation Platform (MATLAB model) developed by the DVB Consortium. Bit-error-rate (BER) graphs are generated to evaluate the overall performance of the system under different levels of signal-to-interference ratio (SIR) and signal-to-noise ratio (SNR). Combinations of multiple interferences onto the system are also implemented. Modifications to the DVB-T2 system (mainly on receiver) such as filtering, are then applied to investigate the feasibility to suppress the effect of interference for improvement in the BER.